Nutrition and depression: Summary of findings from the EU‐funded MooDFOOD depression prevention randomised controlled trial and a critical review of the literature. Issue 4 (15th July 2020) - Owens, M.; Watkins, E.; Bot, M.; Brouwer, I. A.; Roca, M.; Kohls, E.; Penninx, B. W. J. H.; van Grootheest, G.; Hegerl, U.; Gili, M.; Visser, M.; ,
Abstract: This paper discusses the emerging field of nutritional psychology and provides an update on the now completed EU‐funded MooDFOOD depression prevention randomised controlled trial that assessed the effects of two nutrition‐based interventions for the prevention of depression in overweight or obese adults with at least mild symptoms of depression. We first outline the problem of major depression, the most common form of psychopathology and the largest contributor to global disability, and then give an overview of the connection between nutrition and depression; separating the evidence according to prevention and treatment of depression. The extant literature is reviewed, and we examine the implications for both prevention and treatment. Questions are posed for further research in this emerging and important area.